2004
DOI: 10.1016/j.biolcel.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transcriptional regulation in cancer

Abstract: Deregulation of gene expression is a hallmark of the cancer cell. Acquiring a new profile of expressed proteins may enable the cell to re-enter the cell cycle, or give them a growth or motility advantage over "normal cells". An efficient and rapid way to alter gene expression is via regulation of mRNAs already transcribed. Modifications of mRNA stability and/or translational efficiency are increasingly reported in cancer. mRNA stability and translation are controlled through a complex network of RNA/protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
204
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(207 citation statements)
references
References 207 publications
1
204
1
1
Order By: Relevance
“…60 These results are consistent with data demonstrating that inhibition of expression of the Wig-1 ortholog PAG608 using antisense RNA led to attenuated p53-dependent methamphetamineinduced cell death. 20 Most ARE-BPs regulate multiple mRNAs 54,56 , and our preliminary results indicate that Wig-1 also can target other ARE-containing mRNAs apart from p53. 60 …”
Section: Wig-1 Functionmentioning
confidence: 73%
See 3 more Smart Citations
“…60 These results are consistent with data demonstrating that inhibition of expression of the Wig-1 ortholog PAG608 using antisense RNA led to attenuated p53-dependent methamphetamineinduced cell death. 20 Most ARE-BPs regulate multiple mRNAs 54,56 , and our preliminary results indicate that Wig-1 also can target other ARE-containing mRNAs apart from p53. 60 …”
Section: Wig-1 Functionmentioning
confidence: 73%
“…The AREs are elements involved in regulation mRNA stability and translation, and consist of the element AUUUA in various constellations or of exclusively U-rich regions. 53,54 They are present in 5-8 % of the transcriptome, mostly in mRNAs of genes whose expression is precisely controlled, including genes encoding proteins that regulate cell growth or the cellular response to external factors, for example, c-Myc, N-Myc, cyclins, interferons, p53 and p21. 53,54 AREs are generally considered as negative regulators of gene expression.…”
Section: Wig-1 Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Given the important function of RBPs in gene expression, it is not surprising that deregulated or mutated RBPs contribute to cancer progression. [3], [4], [5] Dysfunctional or mutated RBPs can cause increased expression of oncogenes or decreased expression of tumor suppressor genes such as the p53 family members. [6], [7] Recent studies demonstrated that RBPs can protect mRNAs by preventing micro(mi)RNA access to the 3'-UTR and thus protecting them from degradation.…”
Section: Introductionmentioning
confidence: 99%